Community Dynamics and Population Structure of Macro-Zoobenthos: An Evaluation of the Ecological Health of the Snow-Fed Kali River of Uttarakhand, India - Upadhyay, Lata; Verma, Rakesh (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Macro-zoobenthos are aquatic benthic invertebrates that inhabit freshwater ecosystems and act as bioindicators of ecosystem health. This study evaluates the ecological health of the snow-fed Kali River system of Uttarakhand, India, by examining macrozoobenthos taxonomy, diversity, and ecological dynamics. Monthly samples were collected on a yearly basis from three ecologically distinct sites along the river, using stratified sampling methods. Standard methods were used for benthos collection, identification, classification, species diversity, and alpha-beta diversity indices. Taxonomic identification and diversity index analysis revealed 79 genera and 2,458 individuals from three major phyla: Arthropoda (52 families, 76 species), Annelida (1 family, 1 species), and Mollusca (2 families, 2 species). Diversity indices, including Simpson (0.69-0.79), are highest in July and lowest in December. Shannon Wiener (H') index values (1.37 to 1.74) peaked in June and dipped in January. The evenness index (0.66 to 0.80) was highest in July and lowest in December. Margalef Index (0.91 to 1.54) peaked in August and was lowest in January. Equitability index values (0.73 to 0.89) were highest in July and lowest in September. Whittaker's beta diversity analysis yielded a value of 0.4433, signifying substantial dissimilarity in community composition. These findings highlight macrozoobenthos as vital bioindicators, offering key data for river management and biodiversity. They also highlight the need for long-term monitoring and physicochemical integration.